Demon slayer. 7, Trading blows at close quarters - Gotoge, Koyoharu, 1988- (VIZ Media, LLC, 2019)
In Taisho-era Japan, Tanjiro Kamado is a kindhearted boy who makes a living selling charcoal. But his peaceful life is shattered when a demon slaughters his entire family. His little sister Nezuko is the only survivor, but she has been transformed into a demon herself! Tanjiro sets out on a dangerous journey to find a way to return his sister to normal and destroy the demon who ruined his life. Shinobu, Tanjiro, Zenitsu, Inosuke and Nezuko have recovered while under the care of the Demon Slayer Corps. They have even learned a new and powerful technique--Total Concentration! They'll need this new power and all their skill on their next demon-hunting mission aboard the mysterious Infinity Train as it takes them into the dreams of demons!